Lactobacillus buchneri and molasses can alter the physicochemical properties of cassava leaf silage - Archibold G. Bakare; Titus J. Zindove; Arti Bhavna; Ashika Devi; Sereana L. Takayawa; Ami C. Sharma; Paul A. Iji (Heliyon, 2023)
In developing countries where feed resources are scarce, cassava leaves can be used as feed for animals. However, the use of cassava leaves is limited mainly because of their high fibre content and overall acceptability by animals. The resolution to this problem is to process the cassava leaves by ensiling and using additives. Therefore, the objective of the study was to determine the effects of including different inclusion levels of molasses and bacteria concentration on the physicochemical properties of cassava leaf silage. Molasses was added at inclusion levels of 0, 3, 5 and 7 g/100g of the chopped cassava leaves, and Lactobacillus buchneri was mixed with chopped cassava leaves at different concentrations of 0, 3.1 × 106 cfu/ml, 3.1 × 108 cfu/ml and 3.1 × 1010 cfu/ml. The effects of inclusion level of molasses on the colour, smell and texture of cassava leaf silage were significant (P < 0.05). Inclusion of bacteria concentration also influenced the smell of silage (P < 0.05). Effects of the inclusion level of molasses and bacteria concentration resulted in decreased pH, crude protein and crude fibre of silage (P < 0.05). There was a quadratic relationship between Ca and K with inclusion level of molasses in cassava leaf silage (P < 0.05). A positive linear relationship was observed between Mg and molasses inclusion levels in cassava leaf silage (P < 0.05). Using principal component analysis (PCA), molasses had a strong positive correlation with PCA 1, whereas crude fibre, pH and crude protein had a positive correlation with PCA 2. The inclusion level of bacterial concentration was negatively correlated to Ca, CP, P and CF. From the study, the use of molasses and L. buchneri can greatly improve the physicochemical qualities of cassava leaf silage.